The adsorption of copper(II) ions on to dehydrated wheat bran (DWB): determination of the equilibrium and thermodynamic parameters - Özer, A; Özer, D; Özer, A (Elsevier Sci Ltd, 2004)
The adsorption of copper(II) ions on to dehydrated wheat bran (DWB), a by-product of the flour process, was investigated as a function of initial pH, temperature, initial metal ion concentration and adsorbent dosage. The optimum adsorption conditions were initial pH 5.0, initial copper concentration 100 mg l(-1), temperature 60degreesC and adsorbent dosage 0.1 g. The adsorption equilibrium was described well by the Langmuir isotherm model with maximum adsorption capacity of 51.5 mg g(-1) of copper(II) ions on DWB. The observation of an increase in adsorption with increasing temperature leads to the result that the adsorption of copper(II) ions on DWB is endothermic in nature. The thermodynamic parameters such as enthalpy, free energy and entropy changes were calculated and these values show that the copper(II)-DWB adsorption process was favoured at high temperatures. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: adsorption; copper(II); dehydrated wheat bran (DWB); isotherm; thermodynamic parameters